GNSS Meta-Signal Tracking Using a Bicomplex Kalman Filter - Daniele Borio; Melania Susi (Navigation)
Global navigation satellite system (GNSS) signals from different frequencies can be effectively treated as a single entity, characterized by common delays and carrier phases, leading to so-called GNSS meta-signals. A convenient approach for deriving meta-signal acquisition and tracking algorithms has been recently introduced based on bicomplex numbers, which are a bidimensional extension of complex numbers. Bicomplex numbers allow one to represent two signals from different frequencies as a single quantity, providing a compact notation for algorithm development. In this work, an error-state Kalman filter (KF) is developed, and two signals from different frequencies are tracked simultaneously using the bicomplex number paradigm. A triple-loop architecture, in which loop filters are replaced by a single KF, is developed, implemented, and tested using real Galileo alternative binary offset carrier and BeiDou B1I/B1C meta-signals. This analysis clearly shows the advantages of KF tracking for processing GNSS meta-signals with components from different frequencies.